EFL STUDENTS' FOREIGN LANGUAGE ANXIETY IN ENGLISH LANGUAGE ONLINE LEARNING DURING THE COVID-19 PANDEMIC - Friska Debora, - (2021)
Due to the Covid-19 pandemic, the learning system of schools in Indonesia has shifted to an online learning mode. With the swift changes that happened in a short amount of time, students frequently encountered obstacles in their learning process, one of which relates to the foreign language anxiety issues, especially learning English as foreign language. This qualitative study aims to uncover the foreign language anxiety phenomenon experienced by the students and the challenges they encountered along the process. This study was conducted at one of the senior high schools located in South Jakarta, involving two classes of 45 eleventh-grade senior high school students and their English language teacher. This study utilized a questionnaire to 45 students and interviews for the English teacher and seven purposefully select students. The findings of this study show that the students experienced foreign language anxiety while studying English language lessons, adding the challenges for them to engage well in the lesson. The majority of the students mentioned the difficulties they had in adapting rapidly to online learning, along with their fear of making mistakes and the unfamiliarity with the language become the reason for their apprehension feeling in the learning process. The results also showed the coping mechanism students did while facing the obstacles while learning the language was by practicing the breathing exercise, preparing properly before the class started, and asking for help from their teacher and their peers. It was also revealed that the teacher had crucial roles in understanding the students' psychological states better and providing a supportive learning environment.